Alternative Healing as Magical Self-Care in Alternative Modernity - Koch, Anne (Numen, 2015)
Alternative healing, including spiritual healing, unconventional, traditional/folk, and complementary medical treatments, is an increasingly relevant health-care resource in contemporary health-care systems, and a broad, constantly changing, and heterogeneous field of medical pluralism. Some suggestions for classifying spiritual healing as presented in the academic and gray literature are summarized and discussed. The findings are interpreted in terms of the paradigm of alternative modernities. In the direction of, but also in addition to, this paradigm, magic is introduced as a concept to denote certain highly ambiguous occurrences in the alternative modern. Magic is still very much alive and not easy to identify merely as a counterpart of rational, knowledge-generating, disembodying modernity. In this setting, spiritual healing might be seen as a form of magical self-care. Magic is neither modern nor traditional nor irrational per se, but has to be contextualized and described in terms of characteristics like holistic diagnosis, interpersonal congruence, the imaginations of agency, and efficacy.